"Sect, Sectarian, Sectarianism": The Birth, Death, and Resurrection of an Analytical Category in the Study of Western Religions - Moss, Yonatan (Journal of the American Academy of Religion, 2023)
This article charts the changing uses of the interconnected terms sect, sectarian, sectarianist, and sectarianism in the academic study of Judaism, Christianity, and Islam. Following a review of the term sect's early roots in Greco-Roman antiquity and its distinctly Christian transformation, three main steps are analyzed in the genealogy of the category in modern scholarship: (1) deployments by Weber and his early followers; (2) an influential sociological turn in the latter half of the twentieth century; and (3) a sharp decline in the years around the turn of the century in the popularity of sect as a category, followed by a redefinition of its derivative terms (sectarian, etc.) in recent years. Toward the end of the article, lessons are drawn from this genealogy for the future use of the category within scholarship.